INFLATION SURGE OF 2021-2023 AND MONETARY POLICY IN EASTERN EUROPEAN COUNTRIES - Andrei Paslari (Economy and Sociology, 2023)
This article provides an in-depth analysis of the current global economic landscape, with a particular focus on Moldova, Ukraine, Romania, and Poland. The scope of this article is to examine central banks’ responses to the challenges posed by 2021-2023 inflation. The research employs a combination of scientific methods, including empirical analysis and quantitative research. It utilizes data from reputable sources like the World Bank, National Banks, and National Bureaus of Statistics to examine various economic indicators. Statistical software R is used for data analysis, including Cross-Correlation Function (CCF) analysis.